MODELING AND INTELLIGENT ANALYSIS OF KPIS FOR PERFORMANCE INDICATORS OF MANAGEMENT COMPANIES (Uzbekistan Open Conference, 2026)
The article examines the transformation of organizational and economic mechanisms for residential property management through the lens of intelligent data analysis. The author substantiates the transition from static reporting to dynamic KPI modeling as a fundamental decision-making tool. The study reveals the process of converting "raw" data into managerial intelligence, enabling the prediction of infrastructure degradation and financial risks. Particular emphasis is placed on the "domino effect," where technical performance improvements directly correlate with increased collection rates and resident loyalty. Based on the analysis of international expertise and the implementation of the "Mening uyim" platform, the paper proposes predictive maintenance algorithms capable of extending the life cycle of buildings. The research demonstrates that implementing Data-Driven management minimizes operational costs and enhances the investment attractiveness of the housing sector within the digital economy.